(untitled) (Global Journals of Research in Engineering, 2012)
Problem stastement : The digital holography technique, used in measuring the deformations of the scatterers, the process is based on subtraction of interference patterns. A first image is recorded before the deformation of the object in the RAM of a computer, a second followed after deformation. The square of the difference between the two images provides correlation fringes in real time directly observable on the monitor. Results : The interpretation of these fringes to determine the deformation. Conclusion : In this paper, we present experimental results of the variation of diffraction patterns for various displacements of paper.